COMPARISON OF ANTIBACTERIAL ACTIVITY OF GARLIC AGAINST AEROBIC AND ANAEROBIC BACTERIA - DHANUSH, K. G.; UMAMAGESWARI, S. S. M.; MALAVIKA, M.; BHUVANESHWARI, G. (International Journal of Current Pharmaceutical Research, 2021)
Objective: To compare the antibacterial activity of garlic against aerobic and anaerobic bacteria. Methods: Antimicrobial activity of garlic is performed by Agar cup diffusion technique for 3 bacteria Staphylococcus aureus, E. coli and clostridium perfringens. Results: By performing the technique with proper guidance, it is observed that the Staphylococcus aureus specimen shows sensitivity to garlic whereas the other two specimens Escherichia coli and clostridium perfringens doesn’t show any sensitivity to garlic. Conclusion: Due to its vast antibacterial activity of garlic, it can be used along with other antibiotics to increase its efficiency.